2000
DOI: 10.1128/aem.66.12.5123-5127.2000
|View full text |Cite
|
Sign up to set email alerts
|

Biological Role of Xanthomonadin Pigments in Xanthomonas campestris pv. Campestris

Abstract: Previous studies have indicated that the yellow pigments (xanthomonadins) produced by phytopathogenicXanthomonas bacteria are unimportant during pathogenesis but may be important for protection against photobiological damage. We used a Xanthomonas campestris pv. campestris parent strain, single-site transposon insertion mutant strains, and chromosomally restored mutant strains to define the biological role of xanthomonadins. Although xanthomonadin mutant strains were comparable to the parent strain for surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 24 publications
2
59
0
3
Order By: Relevance
“…5) remains to be determined, but on the available evidence they are also likely to act as chorismatases/ 3HBA synthases. For example, the FkbO/RapK homolog in Xanthomonas species (the causative agent of black rot in plants) resides in a gene cluster (44) for the biosynthesis of xanthomonadins, yellow brominated aryl pigments apparently derived via the polyketide pathway from a 3HBA starter unit (45). A block in aroE in the early part of the shikimate pathway abolishes xanthomonadin biosynthesis (46).…”
Section: Phylogenetic Analysis Of Fkbo/rapk Reveals a Superfamily Ofmentioning
confidence: 99%
“…5) remains to be determined, but on the available evidence they are also likely to act as chorismatases/ 3HBA synthases. For example, the FkbO/RapK homolog in Xanthomonas species (the causative agent of black rot in plants) resides in a gene cluster (44) for the biosynthesis of xanthomonadins, yellow brominated aryl pigments apparently derived via the polyketide pathway from a 3HBA starter unit (45). A block in aroE in the early part of the shikimate pathway abolishes xanthomonadin biosynthesis (46).…”
Section: Phylogenetic Analysis Of Fkbo/rapk Reveals a Superfamily Ofmentioning
confidence: 99%
“…oryzae (37), and Xanthomonas campestris pv. campestris (33) are more susceptible to photooxidative damage than are wild-type strains. In vitro, xanthomonadin protects membrane lipids in egg-phosphatidylcholine liposomes against peroxidation (37).…”
mentioning
confidence: 99%
“…[2] Several researchers have reported that some pigmented bacteria, which are rich in carotenoids have been resistant to radiation when subjected to sub-lethal and lethal doses of ionizing radiations, due to the accumulation of the radio-protective pigments in the outer membrane. [3][4][5][6] Carotenoids are the terpenoid pigments produced by a wide variety of plants and microbes, which are reported to have radio-protective property. [7] Carotenoid pigments of bacterial origin have been reported to have radio-protective and antioxidant properties, and as natural coloring agents.…”
Section: Introductionmentioning
confidence: 99%